Seismic behaviour of tunnels: From experiments to analysis. (May 2020) - Tsinidis, Grigorios; de Silva, Filomena; Anastasopoulos, Ioannis; Bilotta, Emilio; Bobet, Antonio; Hashash, Youssef M.A.; He, Chuan; Kampas, Georgios; Knappett, Jonathan; Madabhushi, Gopal; Nikitas, Nikolaos; Pitilakis, Kyriazis; et al.
Highlights: A State-of-the-art review on the seismic response and design of tunnels is presented. Emphasis is placed on recorded responses of actual tunnels during past earthquakes. Relevant recent experimental and numerical studies are discussed. Abstract: The paper presents a state-of-the-art review of the current understanding of the seismic behaviour of tunnels. Emphasis is placed on recorded responses of actual tunnels during past earthquakes, as well as relevant experimental studies. In particular, the observed seismic performance of tunnels is initially discussed, by providing cases of reported damage during past earthquakes. This is followed by a review of the current monitoring systems for this infrastructure, which can be used to create future case studies based on actual recordings of the seismic response. Subsequently, the paper provides a summary of relevant experimental studies that took place in the centrifuge or on shaking tables, followed by a short discussion of current analytical models, simplified methods and numerical schemes for the seismic analysis and vulnerability assessment of tunnels. Throughout the presentation, the current overall gaps in understanding the seismic response of tunnels are identified in an attempt to stimulate further work in these areas by the research community.